SYNTHESIS OF FELDSPAR BICRYSTALS BY DIRECT BONDING - Heinemann S.; Wirth R.; Dresen G. (My University, 2001)
We have produced synthetic feldspar bicrystals using a direct bonding technique. A gem-quality orthoclase crystal from Itrongay, Madagascar, was used for the bonding experiments. Microprobe analysis shows only minor concentrations of iron and sodium. Orthoclase single crystal plates oriented parallel (0 0 1) were cut and chemomechanically polished with silica slurry. From interferometry, final roughness of the square crystal plates was about 0.34 nm. Specimens were wet-chemically cleaned using deionised water. The bonding procedure produced an orthoclase bicrystal with an optically straight grain boundary-oriented parallel (0 0 1), which was investigated by HREM. Along the interface no amorphous layer was observed between lattice fringes of both crystals. We suggest that the bicrystals formed by initial hydrogen bonding and subsequent water loss and polymerisation of silanol and aluminol groups at elevated temperatures.
Keywords: BICRYSTAL SYNTHESIS; FELDSPAR; DIRECT BONDING; GRAIN BOUNDARY